PENERAPAN ALGORITMA K NEAREST NEIGHBOR UNTUK REKOMENDASI MINAT KONSENTRASI DI PROGRAM STUDI TEKNIK INFORMATIKA UNIVERSITAS PGRI YOGYAKARTA - Adi Prasetyo; Kusrini Kusrini; M Rudyanto Arief (Universitas Janabadra, 2019)
The graduation time of a student is very important because it relates to many parties, in addition to the students concerned, guardian lecturers, and program study programs and related parties in the time of student graduation. one of the factors which is the result of graduation from informatics engineering study program students is that many students are wrong in taking thesis titles that are not in accordance with their interests and concentration. So research needs to be done to solve this problem. One way to solve problems is to make predictions. Selection of interest by using student data using Case Base Reasoning (CBR). In this study applying the K-NN Algorithm in determining recommendations in choosing the concentration. The results obtained from this study are by classification using the K-NN Algorithm obtained concentrations that match their interests. Keywords : Predictions, Case Base Reasoning, K-NN Algorithm